Analisis Permainan Gobak Sodor Untuk Menumbuhkan Karakter Kerja Sama PadaPembelajaran Pendidikan Pancasila Siswa Sekolah Dasar Di SDN 1 Keresek - Aindi; Hilman, Irfan; Akmal, Rudi; Tutun Usman, Asep (Jurnal Cahaya Edukasi, 2025)
Cooperation character is an important value that should be possessed by every citizen, especially children at the elementary school level. Character is not formed instantly, but through a continuous learning process. One effort to instill character values can be carried out through contextual activities, such as traditional games in the school environment. This study aims to examine the planning, implementation, as well as the obstacles and solutions in using the Gobak Sodor game as a learning medium to foster the character of cooperation in the Pancasila Education subject. The research method used is qualitative, with data collection techniques including interviews, observation, and documentation. The informants consist of the Principal, Vice Principal for Curriculum, Fourth Grade Homeroom Teacher, Physical Education Teacher, and fourth-grade students. Data analysis in this study was carried out through three stages: data reduction, data presentation, and data verification. The results show that the Gobak Sodor game is effective in developing students' cooperation character. This game is integrated into the learning module through group activities and reflection on the values of cooperation. The obstacles encountered include limited time, weather conditions, and challenges in maintaining discipline and sportsmanship, which were overcome through guidance, time management, and adjustment of the activity location. Overall, this traditional game creates an active, collaborative, and enjoyable learning atmosphere and serves as a contextual learning medium that shapes students' character.